MATHEMATICAL LITERACY ABILITY OF JUNIOR HIGH SCHOOL STUDENTS BASED ON INTRAPERSONAL INTELLIGENCE - Erni Widiyastuti; Desqiana Putri Ramadan; Chumaedi Sugihandardji; Gunawan Gunawan; Jaka Wijaya Kusuma (Yayasan Education and Social Center, 2023)
Mathematical literacy is an individual's ability to use mathematical knowledge to solve everyday problems. This study aims to describe the mathematical literacy ability of junior high school students viewed from intrapersonal intelligence. This research is a qualitative descriptive study with the subject of SMP Negeri 2 Jatinegara students. The purposive sampling technique was employed in the sampling process. Intrapersonal intelligence questionnaires, mathematical literacy tests, and interviews were used to collect data. The questionnaire was used to classify high, medium, and low intrapersonal intelligence students. Tests and interviews were used to describe mathematical literacy skills. The results showed that students with high intrapersonal intelligence had mastered 4 indicators of mathematical literacy: identifying aspects of the problem, turning the problem into an appropriate mathematical image, applying mathematical models to find solutions to problems, and interpreting mathematical solutions/results. Students with medium intrapersonal intelligence had mastered 3 indicators of mathematical literacy: identifying aspects of the problem, turning the problem into an appropriate mathematical image, and interpreting the solution/mathematical result. Students with low intrapersonal intelligence had mastered one indicator of mathematical literacy ability: identifying aspects of the problem